OSTEOPOROTIC FRACTURE IN ADRENAL CUSHING'S: IS IT UNCOMMON? - Ng, KY; Liah, XH; S, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Osteoporosis is a known complication of Cushing's syndrome (CS). The prevalence of osteoporosis due to ndogenous CS has been reported to be 50–59% and about one-third to half of patients with hypercortisolemiainduced osteoporosis experience fragility fracture. We described a case of CS due to Left Adrenal Adenoma complicated with T12 Fracture. RESULTS A 25 year- old Malay female presented with 7 months history of amenorrhea. Clinical examination revealed significant hirsutism, acne, purple striae over abdomen and marked proximal myopathy. Her fasting blood sugar was 8.2 mmol/L. She was treated as Polycystic Ovarian Syndrome (PCOS) by gynaecologist and started on oral contraceptive pill (OCP). She was referred to us for further work up of CS, but it was planned after we wash out the OCP. She was admitted for severe lower back pain with bilateral sciatica. Further history revealed that she had history of fall 3 months earlier but was asymptomatic. Clinical assessment with imaging confirmed T12 fracture with compressive myelopathy involving the nerve roots. Adrenal and spine MRI was done in view of clinical suspicion of CS, which showed that the left adrenal is homogenously enlarged with lobulated margin measuring 2.6 cm x 2.8 cm x 3.0 cm. Her CS was confirmed biochemically with a raised 24-hour Urinary Cortisol at 1345nmol level. Her morning cortisol was 738.2 nmol/L which is elevated while her serum Adrenocorticotrophic hormone was suppressed at <1.10 pmol/L. She proceeded with pedicle screw fixation of her T12 spinal fracture at first and later underwent left adrenalectomy with HPE report of Adrenal Cortical Adenoma with ganglioneuromas. CONCLUSION Literature have shown that osteoporosis is more prevalent in adrenal than pituitary CS. A retrospective analysis has shown that age, body mass index, duration of amenorrhea, extent of hypercortisolism do not significantly affect the prevalence of osteoporosis in CS.